Implementation of Information Technology Utilization Policy in Tegal City Central Java Province - Muhamad Jumadi; Wirman Syafri; Mansyur Achmad; Andi Pitono (CV. Ridwan Publisher, 2023)
The problem is that planning for the development of information and communication technology has not run the pace of development for Tegal City in line with national development planning so that the role of ICT has not been optimal in its implementation and the knowledge, skills and innovative creativity of the Tegal City apparatus, Central Java Province, is still low in the utilization of information technology. The theory used in this study uses Muchlis Hamdi's public policy theory with dimensions: 1) productivity, 2) linearity, 3) efficiency, and the determinant factors that influence supporters and obstacles, 1) substance of the policy, 2) behavior of the executor's task, 3) network interaction, 4) target group participation, 5) resources, policy implementation of information technology utilization in Tegal City, Central Java Province. This study uses a qualitative approach with descriptive methods, namely data collection by interviews, documentation and observation with data analysis, namely data reduction (data reduction), data display (display data), and conclusion drawing/verification (drawing conclusions/verification) with triangulation techniques on the data obtained. Conclusion: the implementation of information technology utilization policies in Tegal City, Central Java Province, is good but not optimal due to problems in the use of SPBE development information technology in the Tegal City government, namely that it has not yet been implemented, not all Human Resources (HR) in OPD The City of Tegal understands the use of information technology, the knowledge, skills and innovative creativity of the Tegal City apparatus and the beneficiaries of community policies, not all layers of Tegal City society can utilize information technology and understand it. The researcher found a new model, namely the name Information Technology Utilization Model